Wealth differences across borders and the effect of real estate price dynamics: evidence from two household surveys - Thomas Y. Mathä; Alessandro Porpiglia; Michael Ziegelmeyer (European Central Bank (ECB), 2014)
Crossing borders, be it international or regional, often go together with price, wage or indeed wealth discontinuities. This paper identifies substantial wealth differences between Luxembourg resident households and cross-border commuter households despite their similar incomes. The average (median) net wealth difference is estimated to be exteuro367,000 ( exteuro129,000) and increases for higher percentiles. Using several different regression and decomposition techniques, spatial (regional) differences in real estate price developments, and thus differences in accumulated nominal capital gains are shown to be one main driving factor for these wealth differences. Other factors contributing to the observed wealth differences are differences in age, income, education and other household characteristics.
Keywords: D31; J61; F22; R23; R31; 330; cross-border commuting; household survey; real estate price dynamics; wealth